Literature's children: the critical child and the art of idealization - Joy, Louise, 1979- (London, UK: New York, USA: Bloomsbury Academic, 2019)
"Literature's Children offers a new way of thinking about how literature for children functions didactically. It analyses the nature of the practical critical activity which the child reader carries out, emphasising what the child does to the text rather than what he or she receives from it. Through close readings of a range of so-called 'Golden Age' novels for children which continue to shape our understanding of what children's literature entails, including The Railway Children, The Wind in the Willows, The Hobbit, and mid-20th-century series fiction, it demonstrates how the child critic resists the processes of idealisation at work in such texts. By bringing together ideas from literary theory and the philosophy of education, drawing in particular on the work of the philosopher John Dewey, it provides a compelling new account of the complex relationships between literary aesthetics and literary didacticism"--
Eighteenth-century poetry and the complexity of the child's mind -- Laughter and the permission to critique -- On seeing : Kate Greenaway's Under the window -- On crying : E. Nesbit's The railway children -- On being (bored) : Kenneth Grahame's The wind in the willows -- On talking : J.R.R. Tolkien's The hobbit -- On loving : Malcolm Saville's Lone pine series.
Includes bibliographical references (pages 217-237) and index.
Keywords: Children's literature, English -- History and criticism; Children -- Books and reading -- History; Reader-response criticism